High incidence of azole resistance among Candida albicans and C. glabrata isolates in Northeastern Iran - Hossein Zarrinfar; Zahra Kord; Abdolmajid Fata (Mazandaran University of Medical Sciences, 2021)
Background and Purpose: Resistance to antifungal drugs is increasing among Candida isolates from patients with vulvovaginal candidiasis (VVC). Lack of correct diagnosis of Candida causing VVC and the experimental use of antifungal drugs are the main causes of this resistance. This study aimed to determine the susceptibility of antifungal drugs against Candida species isolated from VVC in Northeastern Iran.Materials and Methods: Among women suspected of VVC, 189 vaginal dischargespecimens were evaluated. Candida isolates detected by polymerase chain reactionrestriction fragment length polymorphism were examined by standard antifungal diskdiffusion susceptibility testing method for voriconazole, itraconazole, fluconazole, andketoconazole. The susceptibility pattern of these antifungals was reported as sensitive,susceptible dose-dependent, and resistant. The results were evaluated by SPSS software and analyzed by Pearson chi-squared test.Results: Among the vaginal specimens, 108 out of 189 Candida isolates were identifiedas C. albicans, C. glabrata, C. kefyr, C. parapsilosis, and C. tropicalis. The susceptibilityrates of Candida isolates to voriconazole, ketoconazole, itraconazole, and fluconazolewere 92.6%, 90.7%, 68.5%, and 63.9%, respectively. Moreover, the resistance rates tofluconazole, itraconazole, ketoconazole, and itraconazole were 15.7%, 8.3%, 1.9%, and1.9%, respectively. The C. glabrata and C. albicans isolates were resistant to antifungaldiscs among 93% and 20% of the specimens, respectively.Conclusion: The C. glabrata and C. albicans species showed the highest resistance toantifungal drugs. Furthermore, Candida isolates showed the highest sensitivity tovoriconazole and ketoconazole and the lowest sensitivity to fluconazole.